IMPLEMENTASI PERATURAN BUPATI JAYAPURA NOMOR 2 TAHUN 2019 DALAM MENINGKATKAN KINERJA PEGAWAI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN JAYAPURA - Jini Wati (JURNAL KEBIJAKAN PUBLIK, 2020)
The purpose of this study is to describe and analyze the implementation of Perbup No. 2 Years 2019 in the Office of Communication and Information in Jayapura Regency and to analyze the factors that support and hinder employee performance. The research method used is descriptive qualitative to describe and analyze the implementation of Perbup No. 2 Years 2019 in the Department of Communication and Informatics, Jayapura Regency. The technique of determining the informants used was Pusposive, while the data collection included in-depth interviews. Data analysis in the form of data reduction, data display and conclusion. The results show that the first implementation of the Jayapura regent's regulation policy Number 2 of 2019 in improving the performance of the Communication and Information Technology Office has been going well. In terms of communication and information dissemination aspects have been carried out properly, both at the internal level of the agency and disseminating it to other SKPD as is the duty of the Ministry of Communication and Information. In the resource aspect, the Communication and Information Technology dians have quality resources that cover the existing needs of various scientific disciplines, but in terms of quantity it is still lacking, so existing staff help each other in carrying out tasks or a program. Then the office environment is still inadequate to support performance. The disposition is running quite well based on the SOP and the provision of incentives for improving the performance of each staff. And the bureaucratic structure of the division is based on the SOP and the authority and responsibility given in accordance with the main tasks and functions of each existing field and section. Second, the supporting factor is the application of high discipline to maintain motivation to increase employee performance in the Ministry of Communication and Information. Then the inhibiting factor is the problem of conflict and the quality of the existing network is still unstable, which often hinders the performance of staff and employees in the scope of the Kominfo office in Jayapura district.